1999
DOI: 10.1093/pasj/51.6.871
|View full text |Cite
|
Sign up to set email alerts
|

NANTEN Observations of the Pipe Nebula; A Filamentary Massive Dark Cloud with Very Low Star-Formation Activity

Abstract: We present molecular line observations toward the “Pipe Nebula” in the J = 1−0 lines of 12CO, 13CO, and C18O by using “NANTEN” telescope. An area of ∼ 27 deg2 was covered at a 4′ grid spacing with a 2′.7 beam in 12CO. The 12CO velocity-integrated intensity map and channel maps show a filamentary distribution. The total mass of the 12CO- and 13CO-emitting gas is estimated to be ∼ 10000 M⊙ and ∼ 3000 M⊙ , respectively. We have identified 14 C18O cores whose mass is typically ∼ 30 M⊙ . Star formation is active on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 0 publications
12
122
0
Order By: Relevance
“…The raw data were calibrated using the MIR package for IDL that was developed for reduction of SMA data based on the Owens Valley Radio Observatory MMA package (Scoville et al Figure 1 shows the AzTEC/ASTE 1.1 mm FRUIT image obtained toward the north end of the Pipe Nebula. The image shows two dusty clumps which correspond to Core 1 (i.e., B59) and Core 2 detected in a previous low spatial resolution C 18 O(1-0) map (Onishi et al 1999). The clump associated with Core 2 has a filamentary structure ∼0.6 pc long.…”
Section: Sma Data Reductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The raw data were calibrated using the MIR package for IDL that was developed for reduction of SMA data based on the Owens Valley Radio Observatory MMA package (Scoville et al Figure 1 shows the AzTEC/ASTE 1.1 mm FRUIT image obtained toward the north end of the Pipe Nebula. The image shows two dusty clumps which correspond to Core 1 (i.e., B59) and Core 2 detected in a previous low spatial resolution C 18 O(1-0) map (Onishi et al 1999). The clump associated with Core 2 has a filamentary structure ∼0.6 pc long.…”
Section: Sma Data Reductionmentioning
confidence: 72%
“…The crosses, circles, and boxes show the positions of Class-I, flat, and Class-II YSOs, respectively (Forbrich et al 2009). The white circles in panel (a) show the locations and the extents of Core 1 and Core 2 identified by Onishi et al (1999). (A color version of this figure is available in the online journal.)…”
Section: Sma Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore use the HNC 1−0 and 13 CO 2−1 as optically thick tracers for the "infall" signature in Cha III. 13 CO 2−1 likely traces the outer core material (e.g., Onishi et al 1999;Arce et al 2011) and any "infall" signature found with this transition may only correspond to large-scale contraction motions. On the other hand, C 18 O and C 17 O 2−1 were found to correlate very well with the dust extinction between 6 and 15 mag in Cha I (Belloche et al 2011a).…”
Section: Contraction Motionsmentioning
confidence: 96%
“…typically a few times 10 22 cm −2 : c.f. Onishi et al 1999;Tachihara et al 2000); therefore, we can assume that GMCs have rather pancake shape than perfect spherical structure, which suggests that the GMCs' surface area is roughly proportional to their mass. In addition, the amount of HI cloud accumulated onto pre-existing GMCs through the multiple episodes of compression is presumably proportional to the GMC's surface area.…”
Section: Self-growth Termmentioning
confidence: 99%